2018
DOI: 10.3389/fneur.2018.00171
|View full text |Cite
|
Sign up to set email alerts
|

Neurofascin and Compact Myelin Antigen-Specific T Cell Response Pattern in Chronic Inflammatory Demyelinating Polyneuropathy Subtypes

Abstract: ObjectiveThe objective of this study is to investigate whether chronic inflammatory demyelinating polyneuropathy (CIDP) and its subtypes differ in their type 1 T-helper (TH1) cell response against nodal/paranodal neurofascin (NF186, NF155) as well as myelin protein zero (P0 180–199) and myelin basic protein (MBP 82–100).MethodsInterferon-gamma (IFN-γ) enzyme-linked immunospot assay was used to detect antigen-specific T cell responses in 48 patients suffering typical CIDP (n = 18), distal acquired demyelinating… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
14
1
2

Year Published

2018
2018
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 15 publications
(17 citation statements)
references
References 34 publications
0
14
1
2
Order By: Relevance
“…Immune cells Regarding specific immune cells that may be involved in anti-NF155-positive CIDP, one study was interested in studying autoreactive Th1 cell responses against NF155, NF186, P0 (aa 180-199), and myelin basic protein (MBP) (aa 82-100) in typical CIDP and its variants [92]. Using IFN-γ enzyme-linked immunosorbent assay (ELISA), the authors found more instances of IFNγ secretion in response to NF155 by PBMCs derived from typical CIDP patients (9/18 patients) compared to other non-immune neuropathy (ON) patients and healthy controls.…”
Section: Anti-nf155-positive Cidpmentioning
confidence: 99%
“…Immune cells Regarding specific immune cells that may be involved in anti-NF155-positive CIDP, one study was interested in studying autoreactive Th1 cell responses against NF155, NF186, P0 (aa 180-199), and myelin basic protein (MBP) (aa 82-100) in typical CIDP and its variants [92]. Using IFN-γ enzyme-linked immunosorbent assay (ELISA), the authors found more instances of IFNγ secretion in response to NF155 by PBMCs derived from typical CIDP patients (9/18 patients) compared to other non-immune neuropathy (ON) patients and healthy controls.…”
Section: Anti-nf155-positive Cidpmentioning
confidence: 99%
“…In another study in CRPS patients, the number of Tregs did not change, but the specific sub-subset of CD39+ Treg was decreased (Heyn et al, 2019). In contrast, a stronger Th1 response was observed in T cells from patients with neuropathic pain as compared to controls when the cells were stimulated in vitro with myelin-derived antigen (Diederich et al, 2018). Further analysis reported changes in specific markers for sub-subsets of T cells.…”
Section: Phenotype Of Circulating T Cells In Patients With Chronic Painmentioning
confidence: 99%
“…The paranodal localization of NF155 suggests that disruption of the paranodal structure may be necessary before autoantibodies are able to bind in vivo ( 68 , 69 ). Recently, neurofascin and compact myelin antigen-specific T cell response pattern have been analyzed in CIDP subtypes ( 79 ).…”
Section: Pathogenicity Of the Nodal Autoantibodiesmentioning
confidence: 99%